International ratings as a factor of perception of Belarus and neighboring countries - Shebeko, K.K.; Groshev, V.A.; Shabeka, D.K. (Экономика и банки, 2022)
The article puts forward the hypothesis that that the information contained in the ratings, due to its accessibility, prevalence and authority of the rating developers, is taken into consideration by economic agents when making decisions. Such agents include private companies, households, national governments and international organizations. At the same time, the models of bounded rationality (the satisfaction model, the costs model and the reliability model) remain dominant in the behavior of economic agents in the Belarusian economy. The analysis of the results obtained allows to conclude that it is necessary to take measures to improve the image of Belarus, which is formed and broadcasted by international ratings. Using the categories "Satisfaction Model", "Cost Model", "Reliability Model", "National Branding", the impact of international ratings on economic development is analyzed. The influence and perception created by the position of Belarus in international rankings in comparison with Latvia, Lithuania, Poland, Russia and Ukraine on its economic development has been substantiated by creating prerequisites for investment decisions of economic agents and the formation of trends in the international capital market and migration of human capital. Based on the analysis of 33 international ratings, a conclusion was made that Belarus's position in them is a constraining factor in its economic development.